Fathers' Tantrums and Owners' Oppression: Social History in the Narrative in the First Person in Casa Velha, by Machado De Assis - Betella, Gabriela Kvacek [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2022)
Notable as a tipping point in the use of first-person narrators, Casa velha has a structural refinement that is connected to the pervasive representation of Brazilian society in the 19th century. The protagonist alternates the recording of memories with free indirect speech to express the particular joy of his narrative intentions, ideological pretensions and social ascension, while revealing his subordination to the order established in D. Antonia's house, a kind of metaphor order and Brazilian social repressions. We explore the subordinate's voice as a point of view and the intensity of Machado's representation in dialogue with social history.
Keywords: Machado de Assis; Casa velha; point of view